A novel pyroptosis-regulated gene signature for predicting prognosis and immunotherapy response in hepatocellular carcinoma - Zhang, Baozhu; Wang, Zhan (Frontiers in Molecular Biosciences, 2022)
Background: Pyroptosis， a newly discovered programmed cell death, has dual anti-tumor and tumor-promoting effects on carcinogenesis. However, the correlations between pyroptosis-regulated genes and prognosis, immune microenvironment, and immunotherapy response remain obscure in hepatocellular carcinoma (HCC). Methods: We systematically evaluated the alterations of genes on signal pathways regulated by pyroptosis in 363 HCC samples from genetic and transcriptional fields. A risk model consisting of eight genes was built by LASSO-Cox analysis and used for predicting prognoses, clinical features, immune cell infiltration and immunotherapy effect in HCC. Results: We divided HCC patients into high- and low-risk groups based on the risk model. Comprehensive bioinformatics analysis displayed that the high-risk group had shorter lives and less sensitivity to immunotherapy than the low-risk group. We also compared the two risk groups' clinical characteristics and immune infiltration levels. Conclusions: This study demonstrated a vital role of pyroptosis-controlling genes in predicting HCC prognosis and immunotherapy response. The risk model could lay a foundation for pyroptosis-targeted and immune check points-related drugs in HCC.